2009
DOI: 10.1093/jxb/erp210
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate genes affecting Δ9-tetrahydrocannabinol biosynthesis in Cannabis sativa

Abstract: RNA isolated from the glands of a Δ9-tetrahydrocannabinolic acid (THCA)-producing strain of Cannabis sativa was used to generate a cDNA library containing over 100 000 expressed sequence tags (ESTs). Sequencing of over 2000 clones from the library resulted in the identification of over 1000 unigenes. Candidate genes for almost every step in the biochemical pathways leading from primary metabolites to THCA were identified. Quantitative PCR analysis suggested that many of the pathway genes are preferentially exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
105
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(105 citation statements)
references
References 61 publications
(77 reference statements)
0
105
0
Order By: Relevance
“…Many of the genes involved in photosynthesis and carbon fixation are expressed at significant (although not particularly high) levels in the Solanum trichome types investigated, in contrast to what has been observed in some other species (Turner et al, 2000;Gang et al, 2001;Deschamps et al, 2006;Gunnewich et al, 2007;Marks et al, 2009). Therefore, it is likely that at least some of the carbon required for the synthesis of the specialized metabolites found in Solanum glandular trichomes may be fixed within the trichome secretory cells.…”
Section: Resultsmentioning
confidence: 77%
“…Many of the genes involved in photosynthesis and carbon fixation are expressed at significant (although not particularly high) levels in the Solanum trichome types investigated, in contrast to what has been observed in some other species (Turner et al, 2000;Gang et al, 2001;Deschamps et al, 2006;Gunnewich et al, 2007;Marks et al, 2009). Therefore, it is likely that at least some of the carbon required for the synthesis of the specialized metabolites found in Solanum glandular trichomes may be fixed within the trichome secretory cells.…”
Section: Resultsmentioning
confidence: 77%
“…This divergence may reflect the taxonomical distance of hop (Cannabinaceae) from Leguminosae or the difference in enzymatic functions such as different substrate preference. Partial sequence of prenyltransferase putatively involved in cannabinoid biosynthesis has also been found in Cannabis sativa (Cannabinaceae) EST data (34), and this partial sequence is similar to HlPT1. However, the possibility cannot be eliminated that other membranebound prenyltransferases, from the p-hydroxybenzoate prenyltransferase family involved in the biosynthesis of ubiquinone (35,36) and naphthoquinone (19), serve another evolutional origin for those divergent prenyltransferases from other aromatic substrates.…”
Section: Discussionmentioning
confidence: 78%
“…Several Betv1-protein family members function as enzymes in plant natural product biosynthesis (23). High numbers of ESTs corresponding to the DABB protein (9 ESTs) and the Betv1-like protein (6 ESTs) were found in the cannabis trichome EST dataset reported by Marks et al (11).…”
Section: Resultsmentioning
confidence: 96%
“…Several groups have attempted to identify the PKS that synthesizes OA, but the enzymatic basis for this reaction remains unclear (10,11). Taura et al (10) assayed a type III PKS cloned from cannabis leaves and found that it produces olivetol and α-pyrones [pentyl diacetic acid lactone (PDAL) and hexanoyl triacetic acid lactone (HTAL)] but not OA (Fig.…”
mentioning
confidence: 99%